2000
DOI: 10.1385/bter:78:1-3:219
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Liver, Heart, and Spleen Lipid Peroxidation in Rats and Protection by Selenium

Abstract: The purpose of this study was to evaluate the effects of cadmium-induced peroxidative damage to rat liver, heart, and spleen. Sprague-Dawley rats were injected subcutaneously with a single dose of 25, 125, 500, or 1250 microg Cd/kg and evaluated 6, 12, 24, or 72 h later. Liver, heart, and spleen were analyzed for lipid peroxidation and Fe, Cu, Zn, Se, and Cd concentrations. Data showed that Cd produced enhanced lipid peroxidation in the liver, heart, and spleen. These Cd-induced changes were accompanied by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 29 publications
6
36
0
2
Order By: Relevance
“…The elevation in the creatinine was presumably due to nephrotoxic effect of Cd on renal tubules and glomeruli (Abdo and Abdulla, 2013). In support of these findings, it was reported that long-term Cd exposure causes depletion of liver and muscular glycogen, due to its action on the enzymes involved in glycogenesis and energy metabolism (Toury et al, 1985) and induces oxidative stress in the liver and kidney (Yiin et al, 1999). Our results…”
supporting
confidence: 91%
“…The elevation in the creatinine was presumably due to nephrotoxic effect of Cd on renal tubules and glomeruli (Abdo and Abdulla, 2013). In support of these findings, it was reported that long-term Cd exposure causes depletion of liver and muscular glycogen, due to its action on the enzymes involved in glycogenesis and energy metabolism (Toury et al, 1985) and induces oxidative stress in the liver and kidney (Yiin et al, 1999). Our results…”
supporting
confidence: 91%
“…Oxidative stress is one of the mechanisms that contribute to structural changes or misfolding of proteins such as SOD. Lipid peroxidation has been considered as the primary mechanism for cadmium toxicity [Muller, 1986;Yiin et al, 1990;Manca et al, 1999]. It has been proposed that the enhancement of lipid peroxidation by cadmium in rats is a consequence of a decrease in superoxide dismutase and catalase activity [Hussain et al, 1987;Shukla et al, 1989;Stajn et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…For the general population that is mainly exposed by oral and inhalation routes, Kidneys (mainly renal cortex) and liver are considered to be the most susceptible organs in the case of exposure to cadmium [18][19][20] . The soluble salts of Cadmium accumulate in the organism and affect toxically not only the liver and kidneys, but also the brain, lungs, testicles, central nervous system and other tissues [21] .…”
Section: Introductionmentioning
confidence: 99%